Faktor pelindung dalam kalangan remaja di Projek Perumahan Rakyat (PPR) Kuala Lumpur: kajian awalan - Noor Adilah Abdul Rashid; Nor Jana Saim; Ezarina Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2020)
Adolescents living in the People's Housing Project (PPR) is a group that potentially contribute to the nation's development. However most studies about adolescents living in PPR only considered them as at risk, problematic and tend to create chaos in a community. Therefore, this study aims to highlight the protective factors among adolescents living in PPR that can contribute to their positive development. This preliminary study was conducted on 30 respondents living in the People's Housing Project in PPR Kg Kerinchi, Kuala Lumpur. Data were collected using questionnaire the Resilience Youth Development Module (RYDM). The data were then analyzed by using Statistical Package Social Science (SPSS) opted to descriptive analysis to identify the level of protective factors and demographic information of the respondents. Result shows that the protective factors of the respondents is at a high level. Whereas analysis of mean value for each dimension in protective factor indicates that home assets is the highest among respondents which is 26.33. The results of this study are expected to have an impact on awareness of the stakeholders’ about the importance of protective factors or external strengths that may enhance asset and positive development among adolescents especially for those who live in PPR.